Web 2.0 technologies in education - Juškevičienė, Anita (Lietuvos matematikos rinkinys, 2011)
Information technology is a necessity in every activity, so the application of technology in education is expected to improve teaching and learning quality, student motivation and practical and theoretical knowledge aggregation. One of these types of technology are web 2.0 technologies,which are widely used in the world of teaching and learning process. The article analyzes the impact of technology to educational process, gives the varioususes of online technologies for education examples. The paper uses comparative analysis, research and other work synthesis, methods.